2000
DOI: 10.1108/03090560010306197
|View full text |Cite
|
Sign up to set email alerts
|

Added value: its nature, roles and sustainability

Abstract: Access to this document was granted through an Emerald subscription provided by UNIVERSITY OF SASKATCHEWAN For Authors:If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service. Information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comWith over forty years' experience, Emerald Group Publishing is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(143 citation statements)
references
References 29 publications
1
130
0
12
Order By: Relevance
“…This is a very interesting perspective; one of our intentions in developing sensory descriptive labels is that the customer is satisfied with the product and thus acquires the intention to revisit the store and repurchase the product (note that this was not the aim in the present study). Moreover, another effect of this might be that described by de Chernatony and Harris (2000), who declared that this kind of approach may lead to higher consumption, prices, and margins of the product. Wansink et al (2001) also showed that descriptive labels increased sales by more than a quarter and increased the likelihood that customers would purchase the products again on return visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a very interesting perspective; one of our intentions in developing sensory descriptive labels is that the customer is satisfied with the product and thus acquires the intention to revisit the store and repurchase the product (note that this was not the aim in the present study). Moreover, another effect of this might be that described by de Chernatony and Harris (2000), who declared that this kind of approach may lead to higher consumption, prices, and margins of the product. Wansink et al (2001) also showed that descriptive labels increased sales by more than a quarter and increased the likelihood that customers would purchase the products again on return visits.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, consumers may construct their preference on the spot when reading the labels at the point where they must make a choice of what to purchase (Bettman et al, 1998). Sensory description labels de Chernatony and Harris (2000) declared that providing an added value for the consumer might lead to higher prices and higher margins for the selling company. Furthermore, different products will have different sets of sensory characteristics, and the importance of the attributes that are present and communicated could also affect the consumers' willingness to pay (McCluskey et al, 2007).…”
Section: Sensory Descriptions When Comparing Food Productsmentioning
confidence: 99%
“…Womack (2006) stresses that a customer is concerned only with the value addition directed at them and not in the average of the firm's effort in general. For this reason, Chernatony et al (2000) comment that authors such as Band (1991), Gale (1994) and Naumann (1995) have highlighted the element of 'value added (VA)' as a strategy for achieving competitive advantage and have also advised organisations on designing processes that create value for their customers.…”
Section: The Concept Of 'Value' and Vsmmentioning
confidence: 99%
“…The third point is a view of 'value added' as concerned with enhanced strategies, management styles, technologies, special projects or operations (Chernatony and Harris, 2000;Fletcher and Hardill, 1995). An activity or new innovation that makes an organisation thrive becomes value added to the business.…”
Section: Value Added Concept and Value Adding Servicesmentioning
confidence: 99%